DISCOURSE STRATEGIES OF PERSUASION IN POLITICAL SPEECHES - Claire Dubois (International Journal of Literature and Language Studies, 2026)
This article investigates discourse strategies of persuasion in political speeches within the broader field of linguistics and applied language studies. The study uses ten public speeches delivered during election campaigns in English-speaking contexts and applies critical discourse analysis of pronouns, modality, repetition, evaluative adjectives, and narrative appeals. The main finding is that inclusive pronouns, crisis narratives, moral evaluation, and repeated key slogans created alignment between speaker and audience. The article argues that political language should be examined as a strategic construction of collective identity and responsibility. The discussion is relevant to researchers, teachers, curriculum designers, and graduate students who need concise but systematic models of linguistic inquiry.